Clostridial enterocolitis in an emu (Dromaius novaehollandiae) - Hoskins, Emily; Stranahan, Lauren W.; Blue-McLendon, Alice; Rech, Raquel (Brazilian Journal of Veterinary Pathology, 2022)
A 25-year-old female emu (Dromaius novaehollandiae) presented with a 1-week history of lethargy, hyporexia, and recumbency. The bird had lived its entire life at the Winnie Carter Wildlife Center in Texas and had an unremarkable medical history, apart from bilateral congenital blindness.